2016
DOI: 10.1007/s00204-016-1771-2
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in DNA repair genes and putative cancer risk

Abstract: Single nucleotide polymorphisms (SNPs) are the most frequent type of genetic alterations between individuals. An SNP located within the coding sequence of a gene may lead to an amino acid substitution and in turn might alter protein function. Such a change in protein sequence could be functionally relevant and therefore might be associated with susceptibility to human diseases, such as cancer. DNA repair mechanisms are known to play an important role in cancer development, as shown in various human cancer synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 205 publications
(235 reference statements)
0
30
0
5
Order By: Relevance
“…The study of SNPs in cancer has been increasing concomitantly with the interest in cancer genetic susceptibility. Particularly, SNPs in genes known to be implicated in carcinogenic processes have been studied as they may affect susceptibility to several cancer types [26][27][28]. PCa is not an exception, and SNPs of several genes have been studied and identified as putative biomarkers of susceptibility, including genes involved in DNA repair pathways (XRCC4, PMSI, XRCC1 and XPD) [29,30] or growth pathways (VEGF, IGF1 and EGF) [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The study of SNPs in cancer has been increasing concomitantly with the interest in cancer genetic susceptibility. Particularly, SNPs in genes known to be implicated in carcinogenic processes have been studied as they may affect susceptibility to several cancer types [26][27][28]. PCa is not an exception, and SNPs of several genes have been studied and identified as putative biomarkers of susceptibility, including genes involved in DNA repair pathways (XRCC4, PMSI, XRCC1 and XPD) [29,30] or growth pathways (VEGF, IGF1 and EGF) [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological studies have shown that many single-nucleotide variants (SNVs) in DNA repair genes and their intergenic regions are associated with various cancer risks 25 , and that SNVs in inflammation-related genes ( TGF-β1 , TNF , and ILs ), stress response-related genes ( MTHFR and HSPB1 ) and angiogenesis-related genes ( VEGF ) are also involved in the toxicities of radiation therapy 26, 27 , suggesting that it will be difficult for researchers in the field of radiation science to determine whether or not they are involved in individual differences in radiosensitivity. Previously, we developed a TALEN-mediated two-step single-base-pair editing technology in human cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advances in our understanding of SSBR in the past thirty years, there remains much room for expanding our knowledge, as highlighted by the poorly understood basis for the phenotypes observed in defects of SSBR. We recognize, in particular, the need to better grasp the mechanics of sub-pathway choice (such as damage lesion specificity or post-translational modifications [237]), the role of cell type and replicative capacity in SSBR mechanics [305], the protein and organizational differences in nuclear and mitochondrial SSBR [306], and the role of polymorphic SSBR variants in aging and disease [307, 308]. …”
Section: Closing Remarksmentioning
confidence: 99%